Girls just want to have fun? Sexuality, pregnancy, and motherhood among Bolivian teenagers - Mariana Alfonso (Inter-American Development Bank, Research Department, 2007)
This study attempts to quantify female teenage sexual activity, pregnancy, and motherhood in Bolivia using the most recent Demographic and Health Survey. Descriptive results suggest that teenage sexual activity, pregnancy, and childbearing are more prevalent among those adolescents who are more likely to be socially vulnerable and excluded. In addition, the high incidence of undesired pregnancies among Bolivian teen girls suggests that government action to prevent teenage pregnancy is needed. Lastly, the estimation results indicate that not only socioeconomic and demographic factors, but also some of the expected outcomes of teenage motherhood, regional fertility factors, and knowledge about and use of family planning methods, are significantly related to the probability of teenage pregnancy/childbearing.
Keywords: J13; J18; 330; teenage pregnancy; teenage motherhood; rational behavior; Jugendliche; Sexualität; Schwangerschaft; Bolivien